Features of treatment of cancer of the lower ampullary part of the rectum - V Pirogovsky; B Sorokin; S Zlobenet; A Taranenko; A Mylyanovska; D Lutsenko; S Nikogda; M Gnutov (Perioperative Medicine, 2025)
The article analyzes the features of treatment of cancer of the lower ampullary part of the rectum, one of the most common oncological pathologies of the digestive tract. It provides data on morbidity and mortality rates both globally and in Ukraine, highlighting the significance of the issue. The primary objective of the study was to assess the effectiveness of modern surgical methods, including transanal endoscopic microsurgery (TEM) resection, low anterior resection, intersphincteric resection and the use of lumbar bifold reservoirs according to the clinic’s methodology.